In Vitro Toxicity Evaluation of Lignin-(Un)coated Cellulose Based Nanomaterials on Human A549 and THP‑1 Cells - Yanamala, Naveena; Kisin, Elena R; Menas, Autumn L; Farcas, Mariana T; Khaliullin, Timur O; Vogel, Ulla B; Shurin, Galina V; Schwegler-Berry, Diane; Fournier, Philip M; Star, Alexander; Shvedova, Anna A (Biomacromolecules, 2016)
A significant amount of research toward commercial development of cellulose based nanomaterials (CNM) is now in progress with some potential applications. Using human A549 and THP-1 cells, we evaluated the biological responses of various CNMs, made out of similar material but with functional and morphological variations. While A549 cells displayed minimal or no cytotoxic responses following exposure to CNMs, THP-1 cells were more susceptible to cytotoxicity, cellular damage and inflammatory responses. Further analysis of these biological responses evaluated using hierarchical clustering approaches was effective in discriminating (dis)-similarities of various CNMs studied and identified potential inflammatory factors contributing to cytotoxicity. No correlation between cytotoxicity and surface properties of CNMs was found. This study clearly highlights that, in addition to the source and characteristics of CNMs, cell type-specific differences in the recognition/uptake of CNMs along with their inherent capability to respond to external stimuli are crucial for assessing the toxicity of CNMs.